A NOVEL CONCEPT OF HYBRID ELECTRIC PUBLIC BUS WITH POWER MANAGEMENT SYSTEM IN VIETNAM’S CONDITION - Tu, D.T. (Journal of Advanced Manufacturing Technology (JAMT), 2023)
Environmental concerns such as environmental pollution and unnatural climates are drawing the increasing interest of people around the world and being encountered by people in many different countries, especially in the transportation area. In response to this situation, the automotive manufacturing industry is conducting initial research focusing on environmentally friendly vehicles due to the policies and restrictions that are placed in each country. The public bus system is one of the most important solutions for commuting and community building in the inner city to diminish productive air waste of engines. This research implemented a supercapacitor-coupled internal combustion engine power management system in traditional vehicles to tackle the challenges created by output efficiency of existing Vietnam conventional buses. This allowed for the proportion of exhaust released into the environment to be evaluated in conditions that were not optimal, such as when temperature in surrounding area was low. With the use of AMESim platform, it was determined that there is a potential for actual vehicle application in Vietnam with a fuel economy of 33.10%.